An Undergraduate Agroecology Research Fellows Program Engages Co-learning Through Participatory Action Research - Nordstrom, Karen L.; Horner, Catherine E.; Méndez, V. Ernesto; Izzo, Victor; Carpenter, Nell; Faulkner, Joshua W.; Caswell, Martha (Frontiers in Sustainable Food Systems, 2022)
This paper addresses the role of an Undergraduate Agroecology Research Fellows Program (UARFP) toward a more critical and equity-oriented agroecology pedagogy. As a model rooted in action, Undergraduate Agroecology Research Fellows (UARF) become members of the Agroecology and Livelihoods Collaborative (ALC) Community of Practice (CoP), at the University of Vermont; a transdisciplinary research and education group that engages in community-based participatory action research (PAR). Through this model, UARFs support undergraduate student engagement in an advanced agroecology course, through which a PAR process centered on soil health takes place with regional farms. This triangulated learning format involves in-class and on-farm lab work, alongside the embedded UARF enrichment program, through which agroecological principles are examined via inter- and transdisciplinary educational lenses. Within this context, the objectives of the pedagogical research presented in this paper were: 1) To analyze the ALC-UARFP perceptions of transdisciplinary co-learning through PAR, and 2) extract key lessons learned for critical pedagogy, through this model in action. Our methodological results illustrate the strength of participatory inquiry to capture stakeholder perspectives, iteratively informing the program's direction, and providing key lessons learned. Parallel to this evaluative strength, the qualitative results suggest that authentic undergraduate engagement in PAR offers great potential for the development of increasingly transformative educational programs. Further, our UARFP model, grounded in reciprocal and transdisciplinary co-learning within an agroecological community of practice, pushes the praxis needle toward a more comprehensive and critical agroecology pedagogy.